Analisis Isi Pesan Dakwah Ning Imaz Fatimatuz Zahra dalam Video “Keadilan Gender dalam Islam” dalam YouTube NU Online - Puspita, Gita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Justice is the overarching goal of humanity that must berealized and developed continuously to maintain aexisting wholeness. The emergence of gender has shown differences roles, responsibilities, functions and spaces where humans carry out their activities normally. With gender justice, at least humans can relate relationship without any awkwardness between one another. Gender justice also cannot be realized because there are still many valuessociety that places men in a higher rank than women.